Future material demand for automotive lithium-based batteries - Chengjian Xu (Nature Portfolio, 2020)
Lithium-ion-based batteries are a key enabler for the global shift towards electric vehicles. Here, considering developments in battery chemistry and number of electric vehicles, analysis reveals the increasing amounts of lithium, cobalt and nickel that could be needed.